ANALISIS PENGOLAHAN PERMINTAAN DAN KAPASITAS PRODUKSI UMKM BENGKEL TOYO MOTOR - Wahyudi, Haris; Kelvin; Ardiansyah, Rano; Marthin, Ricko; Limgestu, Rico; Sinambela, Fitriana Aidnilla (Transpublika Publisher, 2022)
The Toyo Motor workshop MSMEs was established on January 7, 2019, which is located at Ruko Royal Sincom Blok C No.16. There are many industries around Ruko Royal Sincom, one of which is PT. Panasonic Batam. The number of employees from PT in the industrial area is not small and on average the employees use motorbikes as their means of transportation to go to work. In order to increase the productivity of Toyo Motor's workforce, the MSME owners always understand and maintain good relationships with their employees. By building a good or healthy relationship with the workforce, their performance will also get better. The interview technique used is to prepare several questions for owners that are indirectly related to consumer behavior in service such as the prepurchase stage, service encounter stage, and post encounter stage as well as several other questions regarding the MSME into new information which refers to a conclusion. We use financial statements as data to manage. The author will analyze the effect of implementing the prepurchase stage, service stage and post encounter stage on the increase or decrease in the turnover of Toyo workshop MSMEs. MSMEs have a trend demand pattern where this pattern occurs when there are several customers who like some of the trends that are happening. In today's increasingly competitive era of globalization, it is well understood that the key to winning business competition is to provide quality services that create customer satisfaction.